Proceso de atención de enfermería en paciente con oligohidramnios severo. - Jimenez Maza, Jessica Janeth; Ordoñez Robles, Luis Rodolfo (Machala : Universidad Técnica de Machala, 2019)
INTRODUCTION.- Amniotic fluid is clear yellowish its antibacterial properties help maintain a sterile environment also is intrauterine essential for normal growth and development of the fetus is considered oligohydramnios to decreased volume of less than 5cm amniotic fluid, and when severe oligohydramnios is less than 3 cm, severe oligohydramnios has been associated with an increased risk of neonatal morbidity and mortality as wHO data on the "2015, approximately 303,000 women died of factors related to pregnancy and consequences because only 64% of women receive prenatal care. The general objective of the present investigation is to analyze the case of severe Oligohydramnios of a patient by means of the valuation of the model of Virginia Henderson, evidencing through the investigation of scientific articles and Clinical History. Presentation of the Case: A 19-year-old patient is referred from the Hualtaco Subcenter to the Huaquillas Basic Hospital to perform a follow-up ultrasound, which showed decreased amniotic fluid (0 cm); reason for which she was admitted by emergency and then given to the area of gynecology with pregnancy diagnosis of 20 weeks plus severe oligohydramnios, with stable vital signs, losing amniotic fluid in a small amount. During the first 3 days of hospitalization, special examinations and ultrasounds were performed, which was seen in the affected fetus with bilateral multicystic renal dysplasia, pulmonary hypoplasia, with which it was compatible with the definitive diagnosis of Potter II Syndrome. Method: A literature search was conducted in the following databases, EBSCO, Scielo, Scopus, ScienceDirect and NNNConsult.PubMed Central (PMC), Lilacs, ELSEVIER, ScienceDirect, medlineplus, revistasochog, WHO, PAHO, MSP, apjhs, NCBI, ijpediatrics, journalcra, nutricionhospitalaria, revenfermeria, Results: Several risk factors mainly, nutritional status, age, environment, psychological state, self-medication, which leads to the most important causes with renal dysplasia multicystic bilateral, taking this even severe oligohydramnios because were found not will be producing amniotic fluid or damper leading to have mechanical trauma and fetal malformations, most complications is pulmonary hypoplasia, abnormal contractures of the hands and feet and fetal facial compression, by failing to properly lungs the risk of neonatal mortality developed is higher Conclusions: The Natural History of the Disease, raised by Leavell and Clark, was taken as a basis for a better understanding of severe oligohydramnios, its risk factors, its causes and complications. The model of V. Henderson was perfectly adapted to the present case to be able to perform nursing diagnoses and care plans based on the needs required by the patient, through the search of standardized plans of NANDA, NIC, NOC, what satisfies the general objective stated.
INTRODUCCIÓN.- El líquido amniótico es amarillento transparente sus propiedades antibacterianas ayudan a mantener un ambiente intrauterino estéril además que es esencial para el crecimiento y desarrollo normal del feto se considera oligohidramnios a la disminución del volumen de líquido amniótico menor a 5cm, y oligohidramnios severo cuando es menor de 3 cm, El oligohidramnios severo se ha asociado a un incremento en el riesgo de morbimortalidad neonatal según datos de la OMS en el “2015, aproximadamente 303 000 mujeres fallecieron por factores relacionados con el embarazo y las consecuencias debido a que sólo el 64% de mujeres reciben atención prenatal. El Objetivo general del presente investigación es analizar el caso de Oligohidramnios severo de una paciente mediante la valoración del modelo de Virginia Henderson, evidenciando a través de la investigación de artículos científicos e Historia Clínica. Presentación del Caso: Paciente de 19 años es derivada del Subcentro de Hualtaco al Hospital Básico Huaquillas para realizarse ecografía de control, la misma que se evidenció disminución de líquido amniótico (0 cm); motivo por el cual fue ingresada por emergencia y luego es dada de pase al área de ginecología con diagnóstico de Embarazo de 20 semanas más oligohidramnios severo, con sus signos vitales estables, perdiendo líquido amniótico en poca cantidad. Durante los 3 primeros días de hospitalización se realizaron exámenes y ecografías particulares el cual se vio en el feto afectado con displasia renal multiquística bilateral, hipoplasia pulmonar, con el cual fue compatible con el diagnóstico definitivo de Síndrome de Potter II. Método: Se realizó una búsqueda bibliográfica en las siguientes bases de datos, EBSCO, Scielo, Scopus, ScienceDirect y NNNConsult.PubMed Central (PMC), Lilacs, ELSEVIER, sciencedirect, medlineplus, revistasochog, OMS, OPS, MSP, apjhs, ncbi, ijpediatrics, journalcra, nutricionhospitalaria, revenfermeria, Resultados: Se encontraron varios factores de riesgo principalmente, el estado nutricional, la edad, el ambiente, el estado psicológico, automedicación, el cual lleva a las causas más importantes siendo la displasia renal multiquística bilateral, llevando esto aun oligohidramnios severo debido a que no va haber producción de líquido amniótico ni amortiguador llevando a tener traumas mecánicos y malformaciones fetales , la mayor complicaciones es la hipoplasia pulmonar, contracturas anormales de las manos y pies y compresión facial fetal, al no haberse desarrollado correctamente los pulmones el riesgo de mortalidad neonatal es mayor Conclusiones: Se tomó como base la Historia Natural de la Enfermedad, planteado por Leavell y Clark para un mejor entendimiento del oligohidramnios severo, sus factores de riesgo, sus causas y complicaciones. El modelo de V. Henderson se adaptó perfectamente con el presente caso al poder realizar los diagnosticos de enfermeria y los planes de cuidados basados a las necesidades que requiere el paciente, mediante la búsqueda de planes estandarizados de NANDA, NIC, NOC, lo que satisface el objetivo general planteado.
Keywords: OLIGOHIDRAMNIOS SEVERO; TRATAMIENTO DEL OLIGOHIDRAMNIOS; COMPLICACIONES FETALES; HIPOPLASIA PULMONAR